A Men's Workplace Health Intervention: Results of the POWERPLAY Program Pilot Study. Issue 8 (August 2016) - Johnson, Steven T.; Stolp, Sean; Seaton, Cherisse; Sharp, Paul; Caperchione, Cristina M.; Bottorff, Joan L.; Oliffe, John L.; Jones-Bricker, Margaret; Lamont, Sonia; Medhurst, Kerensa; Errey, Sally; Healy, Theresa
Abstract : Objective: To explore physical activity and eating behaviors among men following the implementation of a gender-sensitive, workplace health promotion program. Methods: Using a pre-post within-subjects design, computer-assisted telephone interviewing (CATI) was used to collect health-related information along with physical activity and fruit/vegetable intake at baseline and after 6 months. Results: At baseline, participants ( N = 139) consumed 3.58 servings of fruit and vegetables/day and engaged in an average of 229.77 min/week moderate-vigorous physical activity (MVPA). At 6 months, daily fruit/vegetable intake did not increase, whereas MVPA increased by 112.3 min/week. Conclusions: The POWERPLAY program successfully increased weekly MVPA. Engaging men in health promotion can be a challenge; here, the workplace served as a valuable environment for achieving positive change.